STUDI KARAKTERISKTIK GELOMBANG PADA FLOATING BREAKWATER TIPE TERPANCANG DAN TAMBAT - Sujantoko Sujantoko; Wisnu Wardhana; Eko Budi Djatmiko; Haryo Dwito Armono; Wahyu Suryo Putro; Rizki Haryono A. (JURNAL TEKNIK HIDRAULIK, 2021)
Floating breakwater (PGT) is designed to be applied as a wave barrier to reduce beach abrasion and wave energy so that waves coming to the beach have their energy reduced. Compared to conventional breakwater structures, PGT structures are more advantageous if the area to be protected from impact waves has a large enough depth. This structure is more flexible because the elevation follows the tides, so this structure can be used as a wharf at the same time. It is also free from the scouring and sedimentation that often occurs on the feet of conventional breakwater structures. This study aims to attenuate and reflect waves from various PGT configurations of piling and mooring types, by testing the physical model of PGT in the wave flume laboratory of the Department of Ocean Engineering ITS, at a water depth of 80 cm, a wave height of 3.5-5.5 cm, a wave period of 0.5-2 seconds, and the angle of the mooring rope (45o, 60o, 90o). PGT is arranged in a variety of longitudinal and transverse directions to the coast. Based on the experiment, it is known that the effect of configuration and width on the PGT structure on wave transmission and reflection is influenced by the mooring angle. Configuration 3 with the largest width can give the best transmission coefficient Kt = 0.797 at 45o mooring angle and reflection coefficient Kr = 0.572 at 90o mooring angle. In type 3 fixed-configuration gives the greatest value Kt = 0.431-0.623 and Kr = 0.053-0.997 compared to other configurations. Because in configurations 1 and 2 the back of the structure is not supported by piles, so a swing occurs which generates waves. While the effect of the slope of the wave, Kt will increase as the number of waves slopes decreases, conversely the value of Kt decreases with the increase in the slope of the wave.Keywords: Floating breakwater, piling, tethered,  mooring